Sleep Disturbance and General Health Status in Patients with Chronic Conditions - Dwi Tama, Tika; Astutik, Erni (KnE Life Sciences, 2021)
Patients with chronic conditions often report sleep disturbance that affects their daily activities and health status. Information about the association between sleep disturbance and general health status in patients suffering from chronic conditions is limited, especially in relation to the developing countries of Asia. This study was conducted to estimate the prevalence of sleep disturbance and its relationship with the general health status of patients with chronic conditions in Indonesia. This crosssectional study included 9,807 patients with chronic conditions who had participated in the Indonesian Family Life Survey (IFLS) wave 5. While sleep disturbance was measured by using the PROMIS sleep disturbance 4a short-form v1.0, general health status was assessed from self-rated health. Multivariable logistic regression was performed to assess the association between sleep disturbance and general health status. The study found that 75.7% of the patients with chronic conditions experienced sleep disturbance. In addition, the odds of being unhealthy among patients with sleep disturbance was 18% higher than those who did not experience sleep disturbance after being controlled by other covariates (p-value = 0.002; AOR 1.18; 95% CI 1.06–1.30). Sleep disturbance was associated with a poor general health status in patients with chronic conditions. Therefore, early detection of sleep disturbance and immediate intervention may lead to better health outcomes in patients with chronic conditions. Keywords: sleep disturbance, health status, chronic conditions, Indonesia